2021
DOI: 10.3389/fpsyg.2021.637060
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Cognition: A Systematic Review

Abstract: Although the influence of social support in health is a widely acknowledged factor, there is a significant gap in the understanding of its role on cognition. The purpose of this systematic review was, therefore, to determine the state-of-the-art on the literature testing the association between social support and cognition. Using six databases (WoS, PubMed, ProQuest, PsycINFO, Scopus and EBSCOhost), we identified 22 articles published between 1999 and 2019 involving an empirical quantitative focus which meet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 132 publications
5
40
0
Order By: Relevance
“…This suggests that posttraumatic growth can follow posttraumatic stress and improve over time, a finding supported by our work. Prior work has shown that increased social support among the elderly is associated with improved cognitive function 66–69 . Further, Stanley et al 70 found that greater perceived organizational support attenuated PTSD symptom severity in US firefighters.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that posttraumatic growth can follow posttraumatic stress and improve over time, a finding supported by our work. Prior work has shown that increased social support among the elderly is associated with improved cognitive function 66–69 . Further, Stanley et al 70 found that greater perceived organizational support attenuated PTSD symptom severity in US firefighters.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot compare this with the literature, given the lack of studies conducted on the oldest-old age group (≥85 years), frequency of contact with friends was identified as an important predictor in this group. A systematic review on the relationship between social support and cognitive functions [ 37 ] reported that social support and cognitive function are positively associated, with emotional support serving as a key dimension. Therefore, these results suggest that active interactions with friends have a preventive effect against cognitive decline among oldest-old individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is defined as structural and functional assistance/help that an individual can receive from family, friends, neighbors, and community members in times of need ( Costa-Cordella et al, 2021 ). According to theoretical models of social support, structural assistance refers to the size and frequency of social interactions; while functional is the quality of relationships, which includes emotional (receiving love, encouragement and positive feedback) and instrumental components (provision of financial help, assistance with childcare, caregiving) ( Southwick et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, positive effects of social support on cognitive performance were described in older adults ( Kelly et al, 2017 ; Costa-Cordella et al, 2021 ). Higher levels of social support have been associated with better cognitive functioning and less cognitive decline ( Seeman et al, 2001 ; Kelly et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%